Unmanned Rotorcraft Systems - Cai, Guowei; Chen, Ben M.; Lee, Tong Heng.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2011)
Unmanned Rotorcraft Systems explores the research and development of fully-functional miniature rotorcraft unmanned aerial vehicles (UAV), and provides a complete treatment of their design. The unmanned system is an integration of advanced technologies developed in communications, computing, and control areas. It is a useful testing ground for trialing and implementing modern control techniques despite the challenges introduced by the limitations on direct scalability between the systems of a small-scale rotorcraft and those of its full-scale counterpart. Included are detailed expositions of: systematic hardware construction; software systems integration; aerodynamic modeling; and automatic flight control system design. Emphasis is placed on the cooperative control and flight formation of multiple UAVs, vision-based ground-target tracking, and landing on moving platforms. Other issues such as the development of indoor micro aerial vehicles (that have to operate without access to a global positioning system) and vision-based navigation are also discussed in depth. The text is rounded out with a presentation of possible future research directions for relevant fields of study. Unmanned Rotorcraft Systems will be of great value to practicing engineers in aerospace-related industries and to academic researchers from aerospace, electrical or mechanical engineering backgrounds working on the development of unmanned systems.
Introduction -- Systematic Hardware construction -- Software System Integration -- Aerodynamic Modeling and System Identification -- Measurement Signal Enhancement -- Automatic Flight Control -- Flight Simulation and Experiment -- Cooperative Control of Multiple Rotorcraft -- Vision-based Tracking and Landing -- Micro Aerial Vehicles -- Future Research.
Keywords: Control engineering; Artificial intelligence; Aerospace engineering; Astronautics; Robotics; Automation; Microprogramming .; Control and Systems Theory; Artificial Intelligence; Aerospace Technology and Astronautics; Robotics and Automation; Control Structures and Microprogramming